Normative values, longitudinal trends and usefulness of adductor dynamometry to detect fatigue in professional rugby league players - Scott, T. J.; Kelly, V. G. (Journal of Australian Strength and Conditioning, 2017)
In rugby league change-of-direction, kicking and running are essential. As such, hip and groin soreness and injuries are common. Dynamometry tests are regularly used to assess adductor strength and monitor groin pain. Test results appear sensitive to changes in acute and chronic training loads (TL), providing further evidence to monitor fatigue. This study aimed to examine the typical error of measurement (TE) and smallest worthwhile change (SWC) of the adductor squeeze test at 60° as well as provide positional differences, normative values and longitudinal trends across a National Rugby League (NRL) season.